Determining the Optimal Number of Cluster Suppliers under Supply Failure Risks - Lee, Shyh-Hwang (International Journal of Supply Chain Management, 2014)
As the risk of supply disruption becomes an important concern for a purchasing company, determining the optimal number of suppliers becomes a top priority in making purchasing decisions to address the supply risk to the manufacturer’s operation. Furthermore, the recently increasing co-location of dedicated supplier clusters has been observed for wider development to reduce supplier numbers, increasing geographical proximity within supply chain networks However, previous studies only discussed the risks of supply disruption in terms of super and unique events, neglecting the probability of the occurrence of a localised semi-super event, which can disrupt all suppliers in a specific geographical location. The present study extends the existing models, allowing a more realistic decision-making process according to the optimal number of cluster suppliers by considering the partial loss associated with independent supply risks in specific geographical regions, which constitute the important components of the overall supply disruption risk. Model comparison and sensitive analysis are conducted on the proposed model. The results indicate that the optimal solution is significantly influenced by the supplier failure probabilities in geographical regions when the ratio of loss versus variable operational cost increases.